THE ROLE OF THE UNITED NATIONS IN PREVENTING HUMAN RIGHTS AND SEXUAL ABUSE IN JAMMU-KASHMIR CONFLICT - Foday Yarbou (UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe conflict between Jammu and Kashmir has acquired a multifaceted character. On one hand, the conflict involves national and territorial contestations between India and Pakistan, and on the other, it entails different kinds of human rights abuses and various political demands by religious, linguistic, regional, and ethnic groups in both parts. This article aims to portrait the images and human rights abuses meted on the people of Jammu and Kashmir. It also urges and pleads to India and Pakistan and all those countries who are taking part directly or indirectly in the territorial disputes or conflict in the region of Jammu and Kashmir to end the conflict. Human rights abuse such as torture, rape, sexual harassment, murder, and unnecessary killings of the people of this region were all condemned by the author of this article. He further requests the international community such as the United Nation to take a bold step in settling the conflict in that region by passing an effective resolution at the international level that will put an end to the conflict. In this article, the author uses a qualitative research method to explore different journals and write up of scholars in finding tangible solutions to the conflict in Jammu and Kashmir. The author also uses a theoretical explanation in the article. The result of this article intends to see that all the main concerning points raised in this write-up are fully considered and implemented by the United Nation in bringing peace and stability in the region of Jammu and Kashmir. Conflict in this region has become a worrying issue in the international community and the necessary steps should be taken to bring it to halt.